Using supplementary reading materials for improving students' reading skill at Thai Nguyen College of mechanics and metallurgy = sử dụng tài liệu đọc bổ trợ để cải thiện kĩ năng đọc của sinh viên trường Cao đẳng Cơ khí - Luyện kim, Thái Nguyên. - Nguyễn, Quỳnh Dương (ĐHNN, 2017)
Chapter 1: Literature Review. Chapter 2: Research Methodology. Chapter 3: Data analysis and Discussion